IMPLEMENTASI METODE DEMONSTRASI DALAM MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS VI SDN 020 KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Yuli Syafni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to determine the use of demonstration methods to improve the learning outcomes of Civicsstudents class VI SDN 020 Kualu Nenas Kecamatan Tambang Kabupaten Kampar. This research was conductedin class VI SDN 020 Kualu Nenas Kecamatan Tambang Kabupaten Kampar.. The form of research is classroomaction research. The subject of this research is the students of Class VI SDN 020 Kualu Nenas KecamatanTambang Kabupaten Kampar. The instrument of data collection used is learning instrument in the form of RPPand syllabus. Based on the result of the research, it is known that the number of students who get score below 70in cycle I is 10 people (33.3%), while in cycle II it decreases to 4 people (13.3%). This situation indicates thatthe improvement of learning on Civics subjects with demonstration methods can be said to be successful,although the completeness of individuals has not been fully achieved, but the mastery of class increased from 76to 80. Based on these results, it can be concluded under the application of demonstration methods can improvestudent learning outcomes class VI SDN 020 Kualu Nenas Kecamatan Tambang Kabupaten Kampar.